Assessment of Telomere Length, Phenotype, and DNA Content. Issue 1 (5th January 2017) - Kelesidis, Theodoros; Schmid, Ingrid
Abstract: Telomere sequences at the end of chromosomes control somatic cell division; therefore, telomere length in a given cell population provides information about its replication potential. This unit describes a method for flow cytometric measurement of telomere length in subpopulations using fluorescence in situ hybridization of fluorescently‐labeled probes (Flow‐FISH) without prior cell separation. After cells are stained for surface immunofluorescence, antigen‐antibody complexes are covalently cross‐linked onto cell membranes before FISH with a telomere‐specific probe. Cells with long telomeres are included as internal standards. Addition of a DNA dye permits exclusion of proliferating cells during data analysis. DNA ploidy measurements of cells of interest and internal standard are performed on separate aliquots in parallel to Flow‐FISH. Telomere fluorescence of G0/1 cells of subpopulations and internal standards obtained from Flow‐FISH are normalized for DNA ploidy, and telomere length in subsets of interest is expressed as a fraction of the internal standard telomere length. © 2017 by John Wiley & Sons, Inc.